2021
DOI: 10.1590/s1413-415220200003
|View full text |Cite
|
Sign up to set email alerts
|

Cobrança pelo uso da água para o saneamento: mecanismos para incentivo a eficiência e atendimento ao uso mínimo

Abstract: RESUMO A cobrança pelo uso da água como instrumento econômico de gestão deve orientar os usuários quanto ao valor do recurso hídrico e incentivar o combate ao uso perdulário. Metodologias recentes inserem mecanismos relacionados às boas práticas no uso da água, mensurado no saneamento por meio do indicador de perdas percentuais na distribuição. Contudo, desprezam-se as perdas ocorridas nas etapas anteriores, bem como a essencialidade do serviço para a sociedade. Usando variáveis que abarcam todo o sistema de a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…For negative answers, there was an increase of 97% for the number of docu- the collection of information, which may be associated with the observed disparity. Several authors have already mentioned that the system's methodological process compromises the reliability and accuracy of the information (CAIÇARA et al, 2022;FARIA et al, 2022;NASCIMENTO;MENDES, 2021;AZEVEDO;JULIEN, 2021). Similar to the results of this study, Faria et al (2022) identified that much information on MBSP made available on the NSIS does not portray reality.…”
Section: Municipal Basic Sanitation Plan Analysis In Absolute Numbers...mentioning
confidence: 99%
“…For negative answers, there was an increase of 97% for the number of docu- the collection of information, which may be associated with the observed disparity. Several authors have already mentioned that the system's methodological process compromises the reliability and accuracy of the information (CAIÇARA et al, 2022;FARIA et al, 2022;NASCIMENTO;MENDES, 2021;AZEVEDO;JULIEN, 2021). Similar to the results of this study, Faria et al (2022) identified that much information on MBSP made available on the NSIS does not portray reality.…”
Section: Municipal Basic Sanitation Plan Analysis In Absolute Numbers...mentioning
confidence: 99%
“…Segundo Santos (2013), nas localizações citadas a tolerância a desvios azimutais é maior, diferente das regiões mais ao sul que demandam maior especificidade no posicionamento dos painéis para obtenção do aproveitamento adequado da irradiação solar. A vantagem adicional da região é a possibilidade de preservar recursos hídricos para o abastecimento cujo processo de universalização enfrenta obstáculos específicos (Aguiar et al, 2020;Teixeira et al, 2021;Teixeira et al, 2023). Apesar disso, todo Brasil conseguiria, em tese, suprir o uso residencial com o advento da energia fotovoltaica, não sendo o fator territorial um limitante.…”
Section: Fonte: Tolmasquim (2016)unclassified
“…Esse risco também está ligado às mudanças climáticas, sendo a água um dos primeiros meios pelos quais a população deve perceber tal fenômeno (ANA, 2016). Em mais, o uso prioritário conferido ao serviço de abastecimento de água (Aguiar et al, 2020;Teixeira et al, 2021) pode estabelecer restrições a geração hidroelétrica não apenas em períodos de escassez, mas também devido a expansão populacional e uso perdulário do recurso.…”
Section: Introductionunclassified
“…The freshwater use charge (FWUC) in Brazil as an economic instrument of watershed management was established in 1997 by Law n. 9.433 (Ferreira et al, 2020). The process and its implementation face administrative bureaucracy, users' discredit, and governance conflicts (Rosa, 2019;De Brito & De Azevedo, 2020;Teixeira et al,2021a). As a result, only six of the thirty interstate Brazilian basins started the process with low prices for withdrawal, effluent discharge, and consumption uses.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 60% of the basin area is semi-arid, facing water governance challenges that result in management decisions used as guidelines for other semi-arid watersheds, such as Paraguaçu Hydrographic Basin (PHB) in Bahia State. In this sense, the arguments that ratify freshwater use charge (FWUC) in SFRB (Teixeira et al, 2021a) find good acceptance in PHB, where the economic instrument is still under discussion.…”
Section: Introductionmentioning
confidence: 99%